Field report PAC 671: optimizing costs and security in the modern accounting / Nurin Athirah Ahmad Nizam - Ahmad Nizam, Nurin Athirah (Universiti Teknologi MARA, Terengganu, 2024)
Muhibbin Associates SDN BHD was established in 2011 under the Companies Act 1965. The company was renamed Muhibbin Group SDN BHD in 2019, and it is currently led by Mr Mohammad Baihaqi Hassanuddin as Managing Director and two other Directors, Mr Khairul Anuar Jamaludin and Mr Luqmannulhakim. The vision of Muhibbin Group Sdn Bhd is to establish a company that offers global corporate services in the areas of secretarial, financial, self-development, and mind. The company's mission is to unite professional and semi-professional workforces in secretarial, financial, taxation, and self development and mind under a single organization while fostering a comfortable work environment and assisting one another in achieving the company's vision. It is located at E-21-1, Blok 3, Jalan Serai Wangi M16/M, Alam Avenue 2, Seksyen 16, 40200 Shah Alam, Selangor.